Main social vulnerability indicators in the COVID-19 pandemic in Iran - Moslehi, Shandiz; Dehdashti, Alireza; Pourmohammdi, Behrad; Fatemi, Farin (Frontiers in Public Health, 2023)
Introduction: Social Factors have the main effect on vulnerability of exposed countries to disasters. COVID-19 pandemic as a disaster is not exception from this fact. The aim of this article is to determine the main social vulnerability indicators in the COVID-19 pandemic in Iran. Methods: This study was conducted in 2021-2022 during three phases including systematic review, virtual panel expert and Analytical Hierarchy Process. First, the draft of social vulnerability indicators in COVID-19 was extracted by a systematic review. Then, the extracted indicators were finalized and prioritized by expert panel and AHP, respectively. Results: Initially, the systematic review found five domains and 38 indicators of social vulnerability in COVID-19. The outcome of expert panel increased the related domains to five, but decreased the indicators to 31. The three prioritized social vulnerability indicators that determined by AHP were population density, accessibility to healthcare facilities and relevant services and vulnerable group. Conclusion: Measuring social vulnerability with identified indicators is valuable to address high COVID-19 incidence among hot spot areas that are socially vulnerable. Regarding to the result of this study, further researches should be conducted to validate the identified indicators.